Over the Horizon : A New Levant - Kulaksiz, Sibel (World Bank, Washington, DC, 2015)
According to a new World Bank report, economic complementarities between Egypt, Turkey, Jordan, Lebanon, Iraq, Syria, and the Palestinian Territories are significant, with substantial welfare gains expected from increased trade and investments and, ultimately, economic integration. With a population of 224 million, a land area of 2.4 million km, a nominal GDP of 1.4 trillion dollars, and close to major markets and transportation corridors, these New Levant countries have significant economic weight and promise. There are opportunities from deeper regional integration to derive significant benefits from economic complementarities and greater competitiveness.